Institusionalisasi Dewan Perwakilan Wilayah Partai Gelora Sumatera Barat sebagai Partai Politik Baru - Maulana, Irvan; Rafni, Al (Journal of Civic Education, 2023)
The existence of political parties is an indicator for improving the quality of a democratic country. The Indonesian People's Wave Party (Gelora) is one of the new parties, which is participating in the realm of politics in Indonesia. The institutionalization of a party can be seen through four dimensions as the process of institutionalizing party: the systemic dimension, value identity, autonomy and the public image. Researchers used descriptive qualitative research methods to describe research results in general. The research informants were determined by means of purposive sampling consisting of political party elements and academics or political observers. The results of the study show that the institutionalization process of the regional leadership council Gelora party of West Sumatra has not run optimally. This can be seen from the work program in the form of political activities. The surge party is in a defensive position and indeed does not want to directly engage in political activities in society. Of the four dimensions for measuring political party institutions, the Gelora party is still improving on the systemic dimension and value identity.